The Effect of Agency Service Quality and Business Innovation on Agency Productivity and its Implications on Customer Loyalty in PT. Pertamina Port and Logistics in Sei Pakning, Riau - Siswanto, Siswanto; Sumali, Bambang; Kwartama, Agung; Malau, April Gunawan (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the impact of agency service quality and business innovation on agency productivity and its implications for customer loyalty at PT. Pertamina Port and Logistics (PPL) in Sei Pakning, Riau. The main issue addressed in this study is how service quality and business innovation can enhance agency productivity and how they influence customer loyalty. The population of the study consists of all customers of PT. PPL, with a sample of 109 respondents selected using purposive sampling with the Slovin formula. The research method used was quantitative with a cross-sectional design, and data collection was carried out through Likert scale questionnaires, which were then analyzed using SmartPLS 4 for validity, reliability tests, and path analysis based on Structural Equation Modeling (SEM). The analysis results show that agency service quality and business innovation have a positive and significant impact on agency productivity. Additionally, agency productivity is proven to mediate the relationship between agency service quality, business innovation, and customer loyalty. These findings suggest that improving service quality and implementing business innovations can strengthen customer loyalty through increased agency productivity. Therefore, it is recommended that PT. Pertamina Port and Logistics continues to enhance its service quality and implement business innovations that improve operational efficiency and customer experience, thus maintaining long-term customer loyalty